KURSUS BIMBINGAN BELAJAR GRATIS SISWA UPT SPF SD NEGERI 104212 MARINDAL II - Friska B. Siahaan; Putri Mekar Sari Sinaga; Rosalina Kacaribu; Sari Sitanggang; Linda Sari Sirait; Sere Megawati Simangunsong (COVIT (Community Service of Health), 2022)
The purpose of implementing this PkM activity is to increase student interest in learning and the quality of student education at SD Negeri 104212 Marindal II through free tutoring courses. Considering how the tendency of children in grades 1, 4, and 5 to have decency, and self-interest, and lack of literacy knowledge, it is hoped that this activity will have a positive and significant impact so that an orderly, safe and comfortable school environment is created. for all his students. The implementation method is carried out from February 2 to 28, 2022 at SD Negeri 104212 Marindal II. After the PkM implementation was carried out, the PkM Team students stated that there were several positive impacts on students at the school, such as: 1) Experience directly the benefits of community service activities through a series of activities that have been carried out, 2) Can help teachers in teaching students, and also 3) Add insight and improve new ways of thinking in solving problems in the school environment. The author hopes that this community service activity can increase the confidence of each participant in daily communication, especially in the school environment as one of the positive activities for the self-development of the participants. Keywords: Courses, free tutoring, effect